Oncostatin M Induction of Monocyte Chemoattractant Protein 1 is Inhibited by Anti-oncostatin M Receptor Beta Monoclonal Antibody KPL-716 - Carl D. Richards; Rohan Gandhi; Fernando Botelho; Lilian Ho; John F. Paolini (Medical Journals Sweden, 2020)
To evaluate cellular response to oncostatin M (OSM) in comparison to interleukin (IL)-31, we analyzed monocyte chemoattractant protein 1 (MCP-1) as a readout for OSM responses with and without IL-4, IL-13, anti-OSM receptor β monoclonal antibody KPL-716, and anti-IL-31 receptor α antibody in human epidermal keratinocytes and human dermal fibroblasts in vitro. In human epidermal keratinocytes, OSM significantly induced STAT3 or STAT1 phosphorylation and synergized with IL-13 or IL-4 in elevating MCP-1. In human dermal fibroblasts, OSM results were similar, and leukemia inhibitory factor or IL-31 minimally activated STAT3 but not MCP-1. OSM significantly stimulated mRNA for type II IL-4 receptor and type II OSM receptor. KPL-716, not anti-IL-31Rα, significantly attenuated MCP-1 response to OSM and OSM + IL-4 in human epidermal keratinocytes and human dermal fibroblasts. OSM, not leukemia inhibitory factor or IL-31, synergized with IL-4 and IL-13 in human epidermal keratinocytes and human dermal fibroblasts, suggesting therapeutic potential of KPL-716 in inflammatory dermatologic diseases distinct from IL-31 inhibition.